Design and in vivo evaluation of selegiline mouth dissolving films - P. Srinivasa Rao; T. Rama Mohan Reddy (International Journal of Pharmacy and Analytical Research, 2022)
The main objective of the present investigation was aimed at formulation and evaluation of Selegiline fast dissolving oral thin films to enhance the patient convenience and compliance in the effective treatment of Parkinson’s disease. Oral thin films of Selegiline were prepared by solvent casting method with using different film forming agents like HPMC5LV, HPMC 15LV, HPMC50LV and HPMC K4M. Propylene glycol, Sucrose, Vanillin is used as a plasticizer, sweetening agent, flavouring agent respectively and citric acid as saliva stimulating agent. FDOFs were evaluated for physical characteristics, Surface pH, weight variation, thickness, folding endurance, percent drug content, percentage elongation, disintegration time, in vitro dissolution studies. Based on all the evaluation studies F18 is selected as optimized formulation and in vitro disintegration time and amount of drug release from the film was 9secs and 99.68% within 7min respectively. A further in vivo study proved that the fast dissolving films of Selegiline produced a faster onset of action and improved bioavailability as compared to the conventional tablets.